Intralesional Triamcinolone Acetonide (TA) Versus Incision and Curettage (I & C) for Medium and Large Size Chalazia - Singhania, Renu; Sharma, Nidhi; Vashisht, Shashi; Dewan, Taru (Nepalese Journal of Ophthalmology, 2018)
Introduction: Chalazion is a common inflammatory mass lesion of eyelid. Incision and curettage is a conventional treatment but intralesional steroid is also a safe option for multiple chalazia and chalazion near lacrimal drainage system. So, we conducted an interventional study to compare the treatment outcomes of injection triamcinolone acetonide (TA) versus incision and curettage (I&C) in medium and large sized primary chalazion. Objective: To compare the success rate of intralesional TA versus I&C for the treatment of medium and large sized primary chalazia. Materials and Methods: An interventional study was carried out in 118 patients with primary chalazion. The patients were divided equally into two groups A and B of medium sized (3-7mm) and large sized chalazia (>7mm) respectively. Treatment modality either I&C or TA was decided in each group by randomization Cytological evaluation was done for each case and diagnosis other than chalazion was excluded. Main outcome measure was resolution in size more than 80%. Secondary outcome measure was correlation of cytological features with size, duration, success rate and complications. Conclusion: Intralesional TA was found to be as effective as I&C in both the groups. In cytological analysis, we found that in large sized chalazia I&C is superior to TA in suppurating granuloma.